(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to see the effect of the application of Articulate Storyline learning media integrated with Biodigital Human Web on the understanding of grade V students of digestive system materials. This study applies a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The total sample involved was 65 respondents from both classes. The selection of both samples was carried out by purposive sampling technique, which is the selection of samples based on certain criteria. In this study, tests and observations were carried out as a data collection technique. The data analysis stage is carried out descriptively and also inferentially to interpret the findings data. The tests carried out in this study include the Wilcoxon test, the Independent Sample T-Test, the Mann-Whitney test, and the N-Gain test. The results of the study showed that there was an effect of the application of learning media on improving student understanding as evidenced by the acquisition of sig scores. = 0.000 < 0.05 which shows that the application of learning media has a significant influence on improving student understanding. Therefore, the application of learning media is very important in learning because it can increase student understanding. The use of Articulate Storyline media that requires an internet connection and the use of English in the Biodigital Human Web are limitations in this study. The next suggestion for researchers is to use applications that can be used without an internet connection and also look for 3D visualizations that use Indonesian